The effects of rapid thermal annealing on the electrical, optical, and structural properties of Nb:TiO2 multilayer electrodes with an inserted nanoscale Ag layer for organic solar cells - Park, Jun-Hyuk; Choi, Yoon-Young; Kim, Han-Ki; Lee, Hyun Hwi; Na, Seok-In (AMER INST PHYSICS, 2010)
We investigated the effects of rapid thermal annealing (RTA) on the electrical, optical, structural, interfacial, and surface properties of Nb:TiO2 (NTO)-Ag-NTO multilayer electrodes inserting a nanoscale Ag layer for application in organic solar cells (OSCs). Up to an annealing temperature of 500 degrees C, the resistivity and optical transmittance of the NTO-Ag-NTO electrodes were stably maintained due to the absence of Ag outdiffusion. The effective activation of the Nb in the NTO layer led to a slight decrease in the resistivity and an increase in the band gap caused by the Burstein-Moss effect. However, increasing the RTA temperature above 600 degrees C resulted in degradation of the NTO-Ag-NTO multilayer electrode due to severe Ag diffusion. Based on the synchrotron x-ray scattering and x-ray photoelectron spectroscopy analyses results, the electrical properties of the NTO-Ag-NTO electrodes are correlated with the microstructure and interfacial diffusion of each layer. In addition, it was found that the performance of the OSC was critically dependent on the RTA temperature of the NTO-Ag-NTO electrodes even though the as-deposited NTO-Ag-NTO electrode had a fairly low resistivity. This indicates that the activation of Nb dopants in the top NTO layer plays an important role in the extraction of carriers from the organic layer to the anode (NTO-Ag-NTO) electrode. (C) 2010 American Institute of Physics. [doi:10.1063/1.3499282]
Keywords: TRANSPARENT CONDUCTING OXIDE; POLYMER; FILMS; EFFICIENT